Resistência à cavitação e erosão por jato de lama de revestimentos binários de WC/Cr3C2 depositados por chama de alta velocidade - Becker, Anderson (2021)
The hydraulic turbines used in hydroelectric power plants for power generation are strongly affected by the flow of water that causes cavitation wear and slurry jet erosion, causing severe damage to the equipment. As a way to reduce these wears, it is possible to use a deposition of coatings that increase the mechanical properties of an equipment. This study used the deposition of binary coatings Cr3C2-37WC-18M and WC-20Cr3C2-7Ni by the HVOF process, with liquid fuel, using two different fuel flows, in order to evaluate the influence of the thermal spray parameters on the properties mechanical (microhardness, indentation fracture toughness and porosity) and roughness after deposition. Cavitation and slurry jet erosion tests were carried out to verify the resistance and wear mechanisms of the samples. It was observed that the increase in fuel flow caused an increase in microhardness values and lower porosity. Phase changes occurred during thermal spraying, with the dissolution of carbides in the metallic matrix and the appearance of complex type carbides (W, Cr)2C being relevant and important for coatings. Indentation fracture toughness was affected by the microstructure of the material, with the Cr3C2-37WC-18M material having lower mean values than that of the WC-20Cr3C2-7Ni material, noting that the dissolution of carbides in the matrix caused fragility which provided lower resistance to crack propagation. For resistance to cavitation, the thermal spray parameters had the greatest influence, with wear starting in the pores. The wear mechanism occurs from the detachment of lamellae from the coating. The resistance to slurry jet erosion was more influenced by the material than by the spray parameters, and the coatings with the highest amount of WC obtained the best results. The wear mechanisms observed were microploughing and microcutting of the metallic matrix, followed by detachment and fracture of the carbides.